2020
DOI: 10.3389/fphy.2020.00327
|View full text |Cite
|
Sign up to set email alerts
|

Stress Evolution in Punch-Through Shear Tests: A Numerical Study Based on Discrete Element Method

Abstract: The discrete element method is adopted to investigate the failure process in punch-through shear tests. The numerical tests agree well with the laboratory tests on crack propagation sequence and the influence of confining stress on effective shear fracture toughness. More importantly, the numerical tests indicate that the increase in axial force first causes stress concentrations. When the stresses reach critical values, cracks initiate and the concentrated stresses dissipate. With further increase in axial di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 33 publications
0
7
0
Order By: Relevance
“…This is of great significance for predicting the residual strength of rocks in acidic environments. After immersing granite samples with different pH values, Liu et al [52] reached a similar conclusion through the uniaxial compression tests.…”
Section: Effect Of Acidification Time On the Strength And Deformationmentioning
confidence: 63%
See 2 more Smart Citations
“…This is of great significance for predicting the residual strength of rocks in acidic environments. After immersing granite samples with different pH values, Liu et al [52] reached a similar conclusion through the uniaxial compression tests.…”
Section: Effect Of Acidification Time On the Strength And Deformationmentioning
confidence: 63%
“…The stronger and faster reaction was caused by the higher concentration of H + in the solution [52,53]. It can be further concluded that stronger acidity led to the destruction of more micro-structures.…”
Section: Mass Damage After Acidificationmentioning
confidence: 88%
See 1 more Smart Citation
“…e flat-joint model can properly simulate the fracture process of rock and rock-like materials [30,31]. In the flat-joint model, tension bond breakages occur when the normal stress between particles exceeds the tensile strength.…”
Section: Numerical Preparationmentioning
confidence: 99%
“…As a filling structure beside the roadway, ordinary concrete has the advantages of high final setting strength, low labor intensity, low cost, and making full use of gangue to reduce the discharge of gangue, but it has the disadvantages of long initial setting time and low initial strength [18]. In terms of surrounding rock deformation, the surrounding rock of gob-side entry retaining in deep mine has the characteristics of rapid deformation, large deformation, and long-term rheological deformation, which is an important reason for the difficulty of retaining roadway along goaf in deep mine [19,20]. erefore, scholars at home and abroad have done a lot of research on surrounding rock control of gob-side entry retaining in deep mine.…”
Section: Introductionmentioning
confidence: 99%